The Flowering of Positive Psychology in Foreign Language Teaching and Acquisition Research - Dewaele, Jean-Marc; Chen, Xinjie; Padilla, Amado M.; Lake, J. (Frontiers in Psychology, 2019)
The present contribution offers an overview of a new area of research in the field of foreign language acquisition, which was triggered by the introduction of Positive Psychology (PP) (MacIntyre & Gregersen, 2012). For many years a cognitive perspective had dominated research in applied linguistics. Around the turn of the millennium researchers became increasingly interested in the role of emotions in foreign language learning and teaching, beyond established concepts like foreign language anxiety and constructs like motivation and attitudes towards the foreign language. As a result, a more nuanced understanding of the role of positive and negative learner and teacher emotions emerged, underpinned by solid empirical research using a wide range of epistemological and methodological approaches. PP interventions have been carried out in schools and universities to strengthen learners and teachers’ experiences of flow, hope, courage, wellbeing, optimism, creativity, happiness, grit, resilience, strengths, and laughter with the aim of enhancing learners’ linguistic progress. This paper distinguishes the early period in the field that started with MacIntyre and Gregersen (2012), like a snowdrop after winter, and that was followed by a number of early studies in relatively peripheral journals. We argue that 2016 is the starting point of the current period, characterized by gradual recognition in applied linguistics, growing popularity of PP and an exponential increase in publications in more mainstream journals. This second period could be compared to a luxuriant English garden in full bloom.